Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.2 Exercises: 74



Work Step by Step

This is an application of both the Sum Rule and the Constant Multiple rule: $g'(x)=(3f(x)-1)'=(3f(x))'+(-1)'=3(f'(x))+0=3f'(x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.